2012
DOI: 10.1242/bio.2012046
|View full text |Cite
|
Sign up to set email alerts
|

HLH-29 regulates ovulation in C. elegans by targeting genes in the inositol triphosphate signaling pathway

Abstract: SummaryThe reproductive cycle in the nematode Caenorhabditis elegans depends in part on the ability of the mature oocyte to ovulate into the spermatheca, fuse with the sperm during fertilization, and then exit the spermatheca as a fertilized egg. This cycle requires the integration of signals between the germ cells and the somatic gonad and relies heavily on the precise control of inositol 1,4,5 triphosphate (IP3)levels. The HLH-29 protein, one of five Hairy/Enhancer of Split (HES) homologs in C. elegans, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…**RT-qPCR results for these genes were previously published [22].ΔThese genes correlate with previously predicted targets of homodimeric HLH-29 [48].…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…**RT-qPCR results for these genes were previously published [22].ΔThese genes correlate with previously predicted targets of homodimeric HLH-29 [48].…”
Section: Resultssupporting
confidence: 54%
“…Of these, 250 genes were up-regulated and 34 genes were down-regulated (Table S1). HLH-29 dependent expression for five of the genes was previously reported [22], and we used RT-qPCR to confirm that expression of 21 additional genes was significantly affected in hlh-29 mutants (Table 1). We found that expression of all of the tested genes was significantly affected in hlh-29 mutants, and that the direction of regulation (up-regulated versus down-regulated) was the same for 20 out of the 26 tested genes.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations